(untitled) (Journal of the College of Basic Education, 2026)
The research titled "The Concept of Control and Its Reflection in Industrial Product Designs"* shed light on numerous developments that have helped design evolve into a process incorporating modern mechanisms governed by a set of control systems. The research problem is formulated through the following question: To what extent is control effective in the design of industrial products? The aim of the research was to examine the mechanisms of control and their impact on achieving effective industrial product designs. After analyzing the research sample, several findings and conclusions were reached, the most important of which are : 1-The design embodied a genuine capacity to enhance organizational control effectively, as a condition realized through a set of rules, standards, and practices. 2-The designs represented a controlling approach in directing technological determinism through the overlap occurring in the design structure, stemming from the emergence of new forms of control based on the degree of disruption introduced by the design